The Lab Must Go On: Clinical Laboratory Management in a World Turned Upside Down - Jackson, Brian R (Am J Clin Pathol, 2020)
OBJECTIVES: The clinical laboratory community has faced unprecedented challenges in responding to the coronavirus disease 2019 (COVID-19) pandemic. Long-held assumptions about laboratory management have been reconsidered in light of these new circumstances. METHODS: Experience during the first 6 months of the COVID-19 pandemic at a clinical reference laboratory was reviewed in the context of several commonly held management principles to assess their relevance to clinical laboratory operations during a crisis. RESULTS: Management and operational ideas regarding different modes of communication, physical proximity and interaction, operating under a fixed budget, and maintaining a breadth of laboratory service offerings have been challenged during the COVID-19 pandemic. The importance of putting people first, maintaining collaboration, and providing effective leadership and communication throughout an organization have been highlighted. CONCLUSIONS: The collaborative activities of highly interdependent teams and individuals have helped the clinical laboratory community respond to society’s needs in the COVID-19 crisis. Not all laboratory management principles apply equally well in the course of an international respiratory pandemic. When navigating crises, leaders need to distinguish situational management principles from those that are universal.